VILLAGE FUND MANAGEMENT STRATEGY FORMULATION USING SOAR AND QPSM ANALYSIS IN KUPANG REGENCY - Martini, Ani; Yektris Killa, Meirgin (Sosiohumaniora, 2021)
Implementing the Village Fund policy focusing on Baumata and Bokong Village, Taebenu District, Kupang Regency, has not provided the expected results. This study aims to formulate strategies for managing the Village Fund. The method used was a qualitative method with a descriptive approach. The research technique used is an interview with the Head and the Secretary of Village Government, Village Enterprises, Community Empowerment Agency, and people of the Villages. In proposing the Village Fund management strategy, SOAR and QPSM analysis tools are used. The results of the analysis formulate strategies that the Village Government can use in managing Village Funds, namely: (1) The Village Fund Budget is adequately managed to accelerate village development, (2) Firm action on the implementation of problematic activities according to regulations, (3) Existing human resources education and training are provided in the Village, and (4) Establishment of Village enterprises involving farmer groups and livestock groups.